Cultural and linguistic barriers to information retrieval and dissemination (2006)
The paper takes a look at culture and language as barriers to information retrieval from libraries and information providers on the one hand, and dissemination of information to library users by these information providers on the other hand. These tend to pose biases in interpretation, analysis and final decision to organize library materials in specific ways. This does occur in cataloguing and classification, sometimes even in the indexing of the materials. Culture has a lot to do in these biases as well, since different cultures provide different language and semantic (semiotic) derivations. The problem is then that of the information user, as research and in turn education of the information user is affected when information retrieval is made difficult. Information dissemination also becomes unsatisfactory when the chips are down. A study of some of the cataloguing practices in academic and public libraries in Nigeria was done. Ten (10) libraries were randomly selected and questionnaires used to elicit information from the cataloguers and indexers. Twenty (20) library users in each of the libraries were also questioned. The results showed that culture and language have effect on both the information providers (cataloguers, indexers) and the information users. Both exhibit biases in their search, provision of information, and eventually dissemination of the gathered information. Recommendations are made on how knowledge organisation can remain a helping rather than hindering factor in information retrieval and dissemination. It is advocated that culture and language be used as enabling factors in this regard and concerted efforts at this are put in educational and research institutions.